Katherine : heart of freedom - Dokey, Cameron; Copyright Paperback Collection (Library of Congress) (New York : Avon Books, 1997)
A young girl saves a patriot from the British as the war for independence grows louder.
"An Avon Flare book."
RL 6.5.
Keywords: Boston (Mass.) -- History -- Fiction; Boston (Mass.) -- History -- Revolution, 1775-1783 -- Juvenile fiction; Love stories